1983
DOI: 10.1111/j.1471-4159.1983.tb11311.x
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Cholinergic Dysfunction in Patients with Dementia

Abstract: Indices of presynaptic cholinergic nerve endings were assayed in neocortical biopsy samples from patients with presenile dementia. For those patients in whom Alzheimer's disease was histologically confirmed, [14C]acetylcholine synthesis, choline acetyltransferase activity and choline uptake were all found to be markedly reduced (at least 40%) below mean control values. The changes occurred in samples from both the frontal and temporal lobes and for [14C]acetylcholine synthesis the decrease was similar under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
1
3

Year Published

1984
1984
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(155 citation statements)
references
References 45 publications
5
146
1
3
Order By: Relevance
“…This loss of function has been hypothesized to depend, at least in part, on the decline in acetylcholine levels and cholinergic neuronal systems (2,12,14,66,72). Cholinergic degeneration is considered to be an important factor underlying memory deficits in neurological disease, such as dementia of Alzheimer's type, and even some Parkinson patients (10,72,74,79). Severity of dementia, number of plaques and, to some degree, loss of synapses, correlate with the degeneration of the cholinergic system in many Alzheimer's patients (27,65).…”
Section: The Cholinergic System and Cognitionmentioning
confidence: 99%
“…This loss of function has been hypothesized to depend, at least in part, on the decline in acetylcholine levels and cholinergic neuronal systems (2,12,14,66,72). Cholinergic degeneration is considered to be an important factor underlying memory deficits in neurological disease, such as dementia of Alzheimer's type, and even some Parkinson patients (10,72,74,79). Severity of dementia, number of plaques and, to some degree, loss of synapses, correlate with the degeneration of the cholinergic system in many Alzheimer's patients (27,65).…”
Section: The Cholinergic System and Cognitionmentioning
confidence: 99%
“…3 Although the involvement of other iueurotransmitter systems is not well established, evidence implicating both a cortical' 8 and a subcortical9-" dysfunction of monoamine neurotransmitter systems has emerged.…”
mentioning
confidence: 99%
“…A shift in thinking about the timing and nature of changes in cholinergic neuron function in aging and disease came about with reports that ChAT activity is unchanged or even increased in the hippocampus and cortex of subjects with MCI (DeKosky et al, 2002;Ikonomovic et al, 2003;Mufson et al, 2003). This is in sharp contrast to reports of large decreases in cholinergic neuron markers and numbers in Alzheimer's disease (Davies, 1979;Francis et al, 1985;Perry et al, 1977;Rylett et al, 1982;Sims et al, 1983). Mechanisms underlying this apparent increase in cholinergic neuron function are unknown, but it was suggested that basal forebrain cholinergic neurons undergo sprouting in an attempt to maintain neurotransmission or to repair entorhinal cortex damage .…”
Section: Cholinergic Neuron Function In Aging Brainmentioning
confidence: 99%